2009
DOI: 10.1128/jcm.00479-09
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Antibodies to VP1 Recognize a Broad Range of Enteroviruses

Abstract: Enteroviruses (EVs) are common seasonal viruses that are associated with a variety of diseases. High-quality monoclonal antibodies (MAbs) are needed to improve the accuracy of EV diagnosis in clinical laboratories. In the present study, the full-length VP1 genes of poliovirus 1 (Polio 1) and coxsackievirus B3 (Cox B3) were cloned, and the encoded proteins were expressed and used as antigens in an attempt to raise broad-spectrum MAbs to EVs. Two pan-EV MAbs were isolated: one raised against Polio 1 VP1 and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 19 publications
2
22
0
Order By: Relevance
“…In IHC, conserved immunogenic regions in the P1 region are utilized for broad-spectrum detection of HEVs. The antibody used in this present study has been shown to react with most but not all HEVs [31, 32]. Because of the limitations with present methods for detection of virus in tissue, it is important that all results, positive as well as negative, are interpreted with caution and are confirmed with several different methods.…”
Section: Discussionmentioning
confidence: 99%
“…In IHC, conserved immunogenic regions in the P1 region are utilized for broad-spectrum detection of HEVs. The antibody used in this present study has been shown to react with most but not all HEVs [31, 32]. Because of the limitations with present methods for detection of virus in tissue, it is important that all results, positive as well as negative, are interpreted with caution and are confirmed with several different methods.…”
Section: Discussionmentioning
confidence: 99%
“…Using an antibody (VP1) that recognizes a large range of HEV species 25 we found positive staining for HEV-B in intestinal epithelial cells of colon biopsies from those six ICD patients that were included in these analyses (Supplementary Figure S3; Supplementary Table S4). In addition, positive staining for HEV was detected in intestinal epithelial cells of colon biopsies from another nine CD patients at the time of diagnosis (patients 10–18; Supplementary Table S4).…”
Section: Resultsmentioning
confidence: 99%
“…In the only EV71 study where cross-reactivity was tested, the MAb raised against the EV71 VP1 protein did indeed cross-react [44]. A blast of the 7C7 epitope on the NCBI database revealed its high specificity: Besides EV71, only CAV16 and the human echovirus 30 sequences carried related epitopes.…”
Section: Discussionmentioning
confidence: 99%